Wild Goose Railroad, vicinity of Nome, Alaska, approximately 1901 - Hegg, Eric A., 1867-1948 (1901)
Railroad built by C.D Lane possibly on the Nome River bridge. Caption on image: "C.D. Lane's R.R. Nome, Alaska" Original photograph by Eric A. Hegg 3033; copied by Webster and Stevens 124.A